2020
DOI: 10.3390/molecules25246048
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Chiroptical Properties of Local Domains in Thin Films of Chiral Silicon Phthalocyanines by CD Imaging

Abstract: The first example of uniformly chiral thin films of silicon phthalocyanines (SiPcs) are reported. The local domains of the films are mapped using circular dichroism (CD) imaging (CDi) technique available at the Diamond B23 beamline. The CDi allowed us to increase the spatial resolution up to 525× when compared with benchtop spectrometers. The results indicate formation on-surface of chiral and stable supramolecular assemblies with homogenous distribution. Chemical functionalization and solvent choice for depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…However, their solid-state films could be conveniently prepared by the drop-casting method, an easy and versatile means for obtaining functionalised surfaces whose properties feature satisfactory reproducibility. As far as the chirality transfer is concerned, the successful outcome depends on a subtle interplay of factors such as, among others, solvent bulk properties (i.e., viscosity, vapour pressure) and the interaction of the molecular substrates with the surface [ 80 , 81 ].…”
Section: Transfer Of Supramolecular Chirality From Solution To Solid ...mentioning
confidence: 99%
“…However, their solid-state films could be conveniently prepared by the drop-casting method, an easy and versatile means for obtaining functionalised surfaces whose properties feature satisfactory reproducibility. As far as the chirality transfer is concerned, the successful outcome depends on a subtle interplay of factors such as, among others, solvent bulk properties (i.e., viscosity, vapour pressure) and the interaction of the molecular substrates with the surface [ 80 , 81 ].…”
Section: Transfer Of Supramolecular Chirality From Solution To Solid ...mentioning
confidence: 99%
“…In order to analyse this further, mapping of the film was performed at 562 nm (λ max J -aggregate), which is shown in Figure 7 . MMP mapping [ 31 , 32 ] of a 5 × 5 grid ( Figure 7 b) revealed that while the films were relatively uniform in terms of absorbance (Abs map), the CD and CB intensities were very small and close to the limit of detection of the instrument. On the other hand, the LD and LB are significantly larger, implying that the refractive index has significantly changed when shifting from solutions to films.…”
Section: Resultsmentioning
confidence: 99%
“…[69] Pantos et al have detected the formation of chiral and stable supramolecular assemblies with homogenous distribution in thin films of silicon phthalocyanines (SiPcs) bearing chiral lateral appendages (chiral naphthalenediimide derivatives or naproxen-based structures). [70] Amabilino and co-workers described a significant heterogeneity in the supramolecular arrangement of dropcasted thin films of a chiral diketopyrrolo[3,4-c]pyrrole dye, functionalized with enantiopure ethyl lactate groups through an ether linkage to the aryl backbone of the chromophore. [71] Finally, Siligardi's group has recently extended the application of SR-ECDi to a large number of thin films of achiral polyvinyl alcohol (PVA) doped with different amounts of enantiopure ddopa, to assess the chiral homogeneity of thin film preparation with potential antimicrobial property.…”
Section: Electronic Circular Dichroism Imaging (Ecdi)mentioning
confidence: 99%
“…Pantos et al. have detected the formation of chiral and stable supramolecular assemblies with homogenous distribution in thin films of silicon phthalocyanines (SiPcs) bearing chiral lateral appendages (chiral naphthalenediimide derivatives or naproxen‐based structures) [70] . Amabilino and co‐workers described a significant heterogeneity in the supramolecular arrangement of drop‐casted thin films of a chiral diketopyrrolo[3,4‐ c ]pyrrole dye, functionalized with enantiopure ethyl lactate groups through an ether linkage to the aryl backbone of the chromophore [71] .…”
Section: Electronic Circular Dichroism Imaging (Ecdi)mentioning
confidence: 99%